Plantar pressures values related with appearance of mechanical hyperkeratosis before and after surgery of mild hallux valgus - Martínez-Nova, Alfonso; Gascó-López de Lacalle, Jaime; Morán-Cortés, Juan Francisco; Pedrera-Zamorano, Juan Diego; Sánchez-Rodríguez, Raquel (Frontiers in Medicine, 2023)
Background: Hyperkeratoses are thickenings of the stratum corneum, provoked by deviation of the ray and excessive plantar pressures. They are very common under the first metatarsal head (MTH) and on the big toe when there exists hallux valgus. The objective of this study was to assess plantar pressures pre- and post-surgery to try to define the threshold values that could determine the appearance of keratopathies. Material and Methods: Seventy-nine patients (100 feet) who had undergone percutaneous distal soft-tissue release and the Akin procedure were evaluated prospectively. The BioFoot/IBV® in-shoe system was used for objective baropodometric functional evaluations of the heel, midfoot, first through fifth MTHs, hallux, and lesser toes. The presence or absence of a hyperkeratosis (HK) or plantar callus under the first MTH or hallux was recorded. The average follow-up time at which the measurements were repeated was 28.1 months. Results: Pre-surgery, 62 feet presented a painful HK on the big toe, while post-surgery, only 9 of the feet presented the same lesion. Patients who presented a prior HK at the first metatarsophalangeal (MTP) joint had a mean pressure of 417.2 ± 254.5 kPa as against a value of 359.6 ± 185.1 kPa for the rest. Post-surgery, these values dropped to 409.8 and 346.3 kPa, respectively. Conclusions: Patients with HK presented an 11% greater mean pressure than those without. The values obtained with the BioFoot/IBV® system in the present study can therefore be considered predictive of the appearance of HK under the first MTH and on the side of the big toe.